A Model for Nonthermal Particle Acceleration in Relativistic Magnetic Reconnection - Xiaocan Li; Fan Guo; Yi-Hsin Liu; Hui Li (The Astrophysical Journal Letters, 2023)
The past decade has seen an outstanding development of nonthermal particle acceleration in magnetic reconnection in magnetically dominated systems, with clear signatures of power-law energy distributions as a common outcome of first-principles kinetic simulations. Here we propose a semianalytical model for systematically investigating nonthermal particle acceleration in reconnection. We show particle energy distributions are well determined by particle injection, acceleration, and escape processes. Using a series of kinetic simulations, we accurately evaluate the energy- and time-dependent model coefficients. The resulting spectral characteristics, including the spectral index and lower and upper bounds of the power-law distribution, agree well with the simulation results. Finally, we apply the model to predict the power-law indices and break energies in astrophysical reconnection systems.